Readiness assessments for gender-affirming surgical treatments: A systematic scoping review of historical practices and changing ethical considerations - Amengual, Travis; Kunstman, Kaitlyn; Lloyd, R. Brett; Janssen, Aron; Wescott, Annie B. (Frontiers in Psychiatry, 2022)
Transgender and Gender Diverse (TGD) are terms that refer to individuals whose gender identity differs from sex assigned at birth. TGD individuals may choose any variety of modifications to their gender expression including, but not limited to changing their name, clothing, or hairstyle, starting hormones, or undergoing surgery. Starting in the 1950s, surgeons and endocrinologists began treating what was then known as transsexualism with cross sex hormones and a variety of surgical procedures collectively known as sex reassignment surgery (SRS). Soon after, Harry Benjamin began work to develop standards of care that could be applied to these patients with some uniformity. These guidelines, published by the World Professional Association for Transgender Health (WPATH), are in their 8th iteration. Through each iteration there has been a requirement that patients requesting cross sex hormones or gender affirmation surgery (GAS) undergo one or more detailed evaluations by a mental health provider through which they must obtain a “letter of readiness,” placing mental health providers in the role of gatekeeper. WPATH specifies eligibility criteria for gender-affirming treatments and general guidelines for the content of letters, but does not include specific details about what must be included, leading to a lack of uniformity in how mental health providers approach performing evaluations and writing letters. This paper aims to review practices related to evaluations and letters of readiness for GAS in adults over time as the standards of care have evolved via a scoping review of the literature. We will place a particular emphasis on changing ethical considerations over time and the evolution of the model of care from gatekeeping to informed consent. To this end, we did an extensive review of the literature. We identified a trend across successive iterations of the guidelines in both reducing stigma against TGD individuals and shift in ethical considerations from “do no harm” to the core principle of patient autonomy. This has helped reduce barriers to care and connect more people who desire it to gender affirming care, but in these authors’ opinions does not go far enough in reducing barriers.